Integration of soft skills in the Universities of Morocco : Focus on intercultural pedagogy - MTAFI Oifâa; TIJJINI , Mustapha (Revue Internationale du Chercheur, 2022)
In the age of globalisation and modernity, it is becoming essential for everyone to acquire human, behavioural and social skills, known as soft skills. In this perspective, intercultural pedagogy is at the heart of the teaching of these so-called transversal skills, as they include different competences such as empathy, solidarity, mutual aid and team spirit. In this context, because societies are increasingly multicultural, intercultural pedagogy cannot be neglected or marginalised. Indeed, it contributes not only to the understanding of the Other, but also to its recognition. Therefore, soft skills are increasingly used in intercultural pedagogy in the professional training of students, since it is essentially about the relationship between identity and otherness. Therefore, the integration of soft skills in intercultural pedagogy is necessary in the sense that students themselves must be made aware of this teaching in their professional training. However, this integration of soft skills into intercultural pedagogy is difficult because it is a new concept for the Professors in charge of these modules. The aim of this article is to demonstrate that teachers themselves need to be equipped with soft skills in order to provide better teaching-learning to their students.